2014
DOI: 10.1177/1082013214539153
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bioactive compounds of black mulberry juice after thermal, microwave, ultrasonic processing, and storage at different temperatures

Abstract: The effect of different sterilization methods (thermal, microwave, and ultrasonic processing) on the main bioactive compounds and antioxidant activity of black mulberry juice during selected storage time (8 days) and temperatures (5, 15, and 25 ℃) was investigated. The antioxidant activity of thermal-treated juice depleted with storage time, whilst both ultrasound- and microwave-treated juices showed transient increase in antioxidant activity during the first 2 days that later decreased with storage time. Lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 34 publications
5
24
0
1
Order By: Relevance
“…In 52 sample of cloudy apple juices (whether or not treated), antioxidant capacity measured by DPPH decreased on average from 5.93 ± 0.2 to 1.6 ± 0.2 mg/g d.w. or almost fourfold. Obtained values are in accordance with research who reported influences of ultrasound (650 W, 20 kHz, D = 6 mm, 30 min, 20°C)and storage (8 days, 15, 15, and 25°C) on black mulberry juice samples with significant reduction in antioxidant capacity(Jiang et al, 2014). Another study demonstrated that sonicated pear juice samples (750 W, 30 kHz, A = 70%, 25, 45, and 65°C, 10 min) had notable decrease in TP and total antioxidant capacity during 21 days of storage at 4°C(Saeeduddin et al, 2017).…”
supporting
confidence: 90%
“…In 52 sample of cloudy apple juices (whether or not treated), antioxidant capacity measured by DPPH decreased on average from 5.93 ± 0.2 to 1.6 ± 0.2 mg/g d.w. or almost fourfold. Obtained values are in accordance with research who reported influences of ultrasound (650 W, 20 kHz, D = 6 mm, 30 min, 20°C)and storage (8 days, 15, 15, and 25°C) on black mulberry juice samples with significant reduction in antioxidant capacity(Jiang et al, 2014). Another study demonstrated that sonicated pear juice samples (750 W, 30 kHz, A = 70%, 25, 45, and 65°C, 10 min) had notable decrease in TP and total antioxidant capacity during 21 days of storage at 4°C(Saeeduddin et al, 2017).…”
supporting
confidence: 90%
“…[35] The type and content of anthocyanins in fruit juices are influenced by fruit varieties and processing techniques. [18,34,36] Pan et al concluded that delphinidin-3-glucoside, petunidin-3-glucoside, and malvidin-3-glucoside were major anthocyanins in blueberry juice. [37] Heat treatment increased permeability and the ability of anthocyanins diffusing into the liquid portion.…”
Section: Resultsmentioning
confidence: 99%
“…However, various research groups have studied how sonication might affect physicochemical and nutritional parameters of products. Generally, low‐power sonication tends to increase the level of bioactive compounds in sonicated food materials due to enhanced extraction of bound pigments as a result of cell wall disruption (Bhat and others ), as reported for kasturi lime (Bhat and others ), black mulberry (Jiang and others ), grapefruit (Aadil and others ), and other juices (Khandpur and Gogate ). Interestingly, Costa and others () evaluated the use of sonicated pineapple juice as a substrate to produce a probiotic beverage containing Lactobacillus casei .…”
Section: Ultrasound Processingmentioning
confidence: 95%